A Critical Look at Women's Role in Physical Education and Sport in the 1930s - Mark Ellner (Educational Considerations, 2020)
This historical research focuses on the role of women in physical education and sport during the 1930s. The purpose is to explore the trends that led to a vast difference between men’s and women’s roles and expectations in physical education and sport during this time period. To engage in effective research of this societal difference, a Feminist Theoretical Framework was employed to analyze primary and secondary sources related to physical education and sports during the 1930s. The research reveals that while sports and physical education became an increasing part of life in the United States during the 1930s, women’s roles and expectations were drastically diminished from those of men. From the intensity levels of physical activity to the rules of the games played, women were seen as an inferior gender within the sports and physical education scope. This article found three main themes leading to the diminished role of women in sports and physical education. They are, cultural views of the 1930s, biologics leading to rules changes, and the sexualization of women athletes. This study contributes to the search for equity in the development of physical education programs and sports programs for women. By revealing past gender roles, a closer examination of current roles becomes clear.
Keywords: physical education; feminist theory; sport; women' s role; sexualization in sport; gender differences